2021
DOI: 10.21203/rs.3.rs-279476/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Analysis of Health Financial Protection in Ghana

Abstract: BackgroundGhana introduced a state sponsored health insurance in 2005. The objectives of risk sharing through a prepaid mechanism was integral to the design, aimed at addressing the inequities in financial protection. Progress, however, has been predictably slow and complicated. The Scheme coexists alongside out-of-pocket spending, resulting in the persistence of catastrophic health expenditures and impoverishment. This study adds to the comparative literature on health financial protection in Ghana.MethodsThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Prior to the uptake of nationwide health insurance scheme in Ghana, it was estimated that 11.0% of households in Ghana spent over 5% of their total household expenditure on healthcare out of pocket (Akazili et al, 2017). Post health insurance coverage using the seventh‐round Ghana Living Standards (GLSS7) by Fuseini et al (2021) revealed a decline in catastrophic health expenditure to 6%, yet households in the bottom quintile allocated a higher share of their total expenditures to health. Available evidence from GLSS7 revealed that rural poor households (0.25%) spend a larger proportion of their total expenditure on out‐of‐pocket health expenditure compared to their non‐poor (0.19%) counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the uptake of nationwide health insurance scheme in Ghana, it was estimated that 11.0% of households in Ghana spent over 5% of their total household expenditure on healthcare out of pocket (Akazili et al, 2017). Post health insurance coverage using the seventh‐round Ghana Living Standards (GLSS7) by Fuseini et al (2021) revealed a decline in catastrophic health expenditure to 6%, yet households in the bottom quintile allocated a higher share of their total expenditures to health. Available evidence from GLSS7 revealed that rural poor households (0.25%) spend a larger proportion of their total expenditure on out‐of‐pocket health expenditure compared to their non‐poor (0.19%) counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Governance, in this context, encompasses the structures and processes used for decision-making and power-sharing in societies, involving dynamic interactions among government, the market, civil society actors, and citizens (Schultz et al, 2015;Lemos and Agrawal, 2006;Rhodes, 1997;Stoker, 1998). The increasing recognition of urban governance's potential in in uencing positive urban development outcomes, especially in developing countries, has led to a more focused analysis of organizational processes and their potential consequences (Hendriks, 2014;Fuseini, 2021). This shift positions (urban) governance as a development paradigm that can address the unstable urban conditions prevalent in the developing world (Yin, 2014;Chen and White, 2021).…”
Section: Introductionmentioning
confidence: 99%